Pengaruh Attitude, Ability, Accountability, Attention, Appearance Terhadap Loyalitas Konsumen Di Hotel Harmoni Langsa - Rona Frenita; Ade Rahma Ayu (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this study was to determine whether there was an influence of attitude, ability, accountability, attention, appearance on consumer loyalty at the Harmoni Langsa Hotel. The sample used in this study was 60 people. all members of the population to be the sample. The analytical method used is descriptive quantitative while the analytical model used in this study is multiple linear regression. While data processing uses SPSS version 25. The results show that the results of the t test state that attitude, attention, partially have a positive and significant effect on consumer loyalty, for the ability variable partially negative and significant effect on consumer loyalty, for the accountability variable partially it does not. effect on consumer loyalty, while the appearance variable partially does not affect consumer loyalty.